Physical and mechanical characteristics of porous asphalt mixture incorporating kenaf fiber - Nur Ezreen, Jasni (2022)
Porous asphalt mixture (PA) also known as open-graded surfaces over a stone bed underneath, allows water to go through. This factor can affect its adhesive strength. The high amount of course aggregate promotes the structure of air voids have certain impacts on the properties of PA. The materials properties are consisting of both aggregate and bitumen tests. This study details out the aggregates by sieve analysis test in order to develop new aggregate gradation for PA that known as New Gradation of Porous Asphalt mixture (NPA). This research also evaluates the morphological and chemical analysis and determine the engineering properties of modified porous asphalt mixture incorporating kenaf fiber. The test on the binder includes the softening point, penetration, and ductility. Sieve analysis was done based on five (5) ASEAN countries' aggregate gradation to obtain the gradation for NPA. The countries included are Malaysia, Vietnam, Thailand, Singapore, and Indonesia. Morphological and chemical test including Scanning Electron Microscopy (SEM), X-ray Diffractions (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) in order to examine the interior structure of the PA mixture. While, mechanical performance test for PA were conducted to analyze the main problems of PA using Marshall stability test, Permeability test, Binder Draindown test and Cantabro Loss test to identify the strength and the properties of the conventional PA with the addition of kenaf fiber compared to the new gradation of PA incorporating kenaf fiber. From the analysis, Singapore specification have all the criteria in terms of aggregate gradation for fine aggregate and the rest are from Thailand aggregate specification for lower line while for upper line, Vietnam specifications were proved to have all the criteria within all five countries gradations. The addition of 0.3% kenaf improved the performance of the PA. The results showed that the fibers improved the mechanical properties of the modified and control asphalt mixture. The use of kenaf fibers in PA could enhance the performance of asphalt pavements against common distresses as rutting, raveling and fatigue. The outcome of this study is anticipated to contribute better and more durable PA than the current PA design in especially for tropical country like Malaysia.